Perioperative Safety of Combined Augmentation-Mastopexy: An Evaluation of National Database. Issue 5 (November 2021) - Ali, Barkat; Choi, EunHo Eunice; Barlas, Venus; Nuzzi, Laura; Morrell, Nathan T.; Labow, Brian; Borah, Gregory; Taghinia, Amir
Abstract : Introduction: The safety of combined augmentation-mastopexy is controversial. This study evaluates a national database to analyze the perioperative safety of combined augmentation-mastopexy to either augmentation or mastopexy alone. Methods: The American College of Surgeons National Surgical Quality Improvement Program database was queried to identify patients undergoing augmentation mammaplasty and mastopexy from 2005 to 2018. The patients were divided into the following groups: group I, augmentation; group II, mastopexy; group III, combined augmentation-mastopexy. Baseline characteristics and outcomes were compared. Outcomes were 30-day complications, reoperation, and readmission. Results: We found 5868 (74.2%) augmentation only, 1508 (19.1%) mastopexy only and 534 (6.6%) combined augmentation-mastopexy cases. Mean operative time was highest among the combined group at 129 minutes compared with 127 minutes for mastopexy alone and 66 minutes for augmentation alone ( P < 0.01). Rates of any complications and readmission were different among groups (0.8% vs 2.5% vs 1.5% respectively, P < 0.01 and 0.7% vs 1.5% vs 1.5% respectively, P = 0.049), whereas reoperation was not statistically different (1.2% vs 1.4% vs 1.5%, P = 0.75). The incidence of dehiscence (0.6%; P < 0.01) was highest in the combined group. Multivariable logistic regression analysis did not reveal an increased odds of complications, reoperation, or readmission with combined augmentation-mastopexy. Conclusions: An evaluation of the nationwide cohort suggests that combined augmentation-mastopexy is a safe procedure in the perioperative period.